Prenatal Diagnosis of Arhinia - Gregory E. Zemtsov; Anthony E. Swartz; Jeffrey A. Kuller (American Journal of Perinatology Reports, 2022)
Arhinia is a rare congenital anomaly that is not typically associated with known genetic mutations and is usually discovered after an affected infant is born. Prenatal diagnosis is important because neonates with arhinia often require specialized respiratory support with creation of an artificial airway. We present a case of isolated arhinia diagnosed on second-trimester ultrasound. A patient presented for routine ultrasound at 18 weeks gestation, and nasal tissues were absent in an otherwise morphologically normal appearing fetus. Cell free fetal DNA was unremarkable. The patient elected to undergo termination of pregnancy by dilation and evacuation. Subsequent genetic analysis confirmed a normal fetal karyotype and microarray, and no examination of fetal structural anatomy was possible. Antenatal diagnosis of arhinia is important to guide maternal–fetal care decisions and requires methodical sonographic evaluation to identify this malformation prior to delivery.